The Effect of Compaction Pressure and Matrix Percentage on the Properties of Phenolic Resin-Metal Powder-RHA Hybrid Composites for Brake Pads - Sukanto, Sukanto; Ardiansyah, Ardiansyah; Erwanto, Erwanto; Budi, Abdul; Wanto, Agus (Universitas Sultan Ageng Tirtayasa, 2026)
This study aims to analyze the effect of compaction pressure variation and matrix percentage on the mechanical and physical properties of phenolic resin–metal powder–RHA hybrid composites as an alternative non-asbestos brake pad material. The composite manufacturing process was carried out using the powder metallurgy method, which included milling, compaction at pressures of 5000, 5300, and 5600 psi, and sintering at a temperature of 130°C for 10 minutes. The tests included Brinell hardness based on ASTM E110-14 and density using the Archimedes method according to ASTM B962-17. The results showed that an increase in compaction pressure had a significant effect on increasing both hardness and density. Optimal conditions were obtained at a pressure of 5600 psi and a matrix fraction of 35%, resulting in a hardness of 103.77 HB and a density of 1.54 g/cm³. These values meet the standards for commercial brake pad materials, namely a hardness of 65–105 HB and a density of 1.5–2.5 g/cm³. Thus, the developed hybrid composite has the potential to be used as an environmentally friendly brake pad material to replace asbestos. Further research is recommended to examine the tribological properties and wear resistance to ensure the performance of the material under actual working conditions.